FROM RELIGIOUS MODERATION TO PROPORTIONAL RELIGIOUS FREEDOM (ARABIC STYLISTICS IN RISALAH AHLUSSUNNAH WALJAMAAH BY HASYIM ASY'ARI) - Nasiruddin, Nasiruddin (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
Freedom of religion is a fundamental principle in Pancasila and the 1945 Constitution. However, its interpretation is often confronted with tensions between religious conviction and respect for diversity. KH. Hasyim Asy'ari's ideas in Risalah Ahlusunnah wal Jama'ah (RAJ) offer a model of religious moderation that is relevant to this context. This study aims to reveal the characteristics of Arabic stylistics used by KH. Hasyim Asy'ari, in promoting religious moderation, also examines the characteristics of religious freedom that can be developed in Indonesia based on his concept of religious moderation. The method used is qualitative analysis based on text study with an Arabic stylistic approach. The primary source is the RAJ book, which is then analyzed using Arabic stylistics theory and reinforced with analysis from similar studies. The results show that KH. Hasyim harmoniously combines the styles of taqr?r? (affirmation), ta?dh?r? (warning), and du'?'? (supplicatory). This combination produces a pattern of religious communication that is firm yet gentle. KH. Hasyim's thinking affirms the limits of faith and criticizes deviations from doctrine, yet closes with a prayer that the people be kept from error. This style reflects Islamic moderation in line with the principles of religious freedom, as outlined in Pancasila and the 1945 Constitution. Religious freedom in the Indonesian context is not absolute. The exercise of religious freedom is grounded in moral responsibility and the preservation of social harmony. Thus, KH. Hasyim's language functions not only as a tool for preaching but also as a means of shaping civilized religious ethics.